The pathogenesis, diagnosis, and treatment of chronic endometritis: a comprehensive review - Yan, Xinyang; Jiao, Jiao; Wang, Xiuxia (Frontiers in Endocrinology, 2025)
Chronic endometritis (CE) is a subtle but persistent inflammatory disorder of the endometrium that is often underdiagnosed due to its asymptomatic or non-specific presentation. The etiology of CE primarily involves microbial infections and immune dysregulation, often accompanied by microbial dysbiosis. Diagnosis relies on histopathological examination, especially the identification of stromal plasma cells, alongside hysteroscopic findings and microbiological testing, though standardization remains lacking. Mechanistically, CE-induced infertility stems from altered immune cell profiles, impaired endometrial receptivity, aberrant decidualization, dysbiosis of the endometrial microbiota, and abnormal uterine peristalsis. Aberrant gene expression and hormone receptor dysregulation further disrupt the implantation window. This review summarizes current understanding of the diagnostic criteria, pathogenic mechanisms, and therapeutic strategies for CE, emphasizing its crucial role in infertility and the need for standardized clinical management.